PENGARUH AKUNTABILITAS PELAYANAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KOTA BATAM - Dian Lestari Siregar (LPPM Universitas Putera Batam, 2018)
Tax is one of the main sources of revenue of the state, where the tax revenue is utilized for national and regional development. The government continues to increase revenues from the tax sector and one of them is revenue from the local tax sector. One source of local tax revenue is the Motor Vehicle Tax (PKB). Batam City which is an industrial city becomes its own maghnet for the population of productive age especially residents outside the city of Batam, which causes the increase in number of residents of Batam from year to year. The increase in population has an effect on the number of motor vehicle demand to facilitate economic activity, plus the number of credit offer from various trade associations, so that the number of motor vehicles in Batam continues to increase, the final impact is the acceptance of Motor Vehicle Tax (PKB). Acceptance Batam City PKB has increased significantly, but the achievement is not accordance with the targeted by the government of 100 percent. Achievement is only 50-52 percent, which means the government efforts are not optimal. The lack of optimization is one of the caused why the compliance of taxpayers of motor vehicle is low. The aim of this study is to see the impact of Service Accountabilit and Sanctions to taxpayer compliance in paying motor vehicle taxes in Batam. This research uses quantitative descriptive method with sampling technique using purposive sampling and than calculated with slovin formula. The number of samples obtained by 100 respondents. Data analysis using multiple linear regression analysis. The results showed that accountability of public services has no significant effect on taxpayer compliance. While tax sanction have a positive and significant impact on taxpayer compliance.